Ke-kere African Management Model: Galvanizing the Management DNA - Don-Solomon, Amakiri (INTI International University, 2023)
Several years after conceptualization of management thoughts a great gap and deep silence still engulf the African perspective to management, this could not have been far-fetched but for the fact that earlier conceptualization of management thoughts was westernized. This paper’s focus is to corroborate concerns raised by African scholars for the dare need of African perspective to management thoughts and espouse a functional proposition that leverage management thoughts in the African context. The paper evaluates classical management theories which formed the foundation of management thoughts; it further examined the western characteristics of these theories. After reviewing existing African management concepts, the paper developed a new model in African management thoughts known as the Ke-kere African management model, the underlying philosophy of this model is that “organization needs are insatiable” thereby corroborating the lean-management concept. After making effort to see classical management theories applicability in Africa, the paper concludes that although classical management theories have western characteristic but has immensely contributed to management practices in Africa till date; economic industrial democracy popularly known as management by objective, bureaucratic management theory which serve as the operative framework of the Nigerian Civil Service are few instances to mention.